Performance and Risk Assessment of Honeypots on IoT and VPS Using COBIT 2019 and Stress Test - Purnama, Lukas Hadi; Daniel Hary Prasetyo (Journal of Computer Networks, Architecture and High Performance Computing, 2025)
The massive wave of digital transformation has increased the complexity of cyber threats, particularly targeting vital network services. Honeypots have emerged as an effective approach for detecting and analyzing attacks, yet platform selection and management strategies remain a challenge. This study analyzes the performance, management, and risks of two types of honeypots, Cowrie (medium interaction) and Heralding (low interaction), implemented in different computing environments, based on the COBIT 2019 framework (domains EDM03, APO12, and DSS05). Evaluation was conducted through experiments on SSH, Telnet, FTP, SMB, MySQL, and HTTP services, utilizing both isolated and multistage honeypot scenarios. The results show that both honeypot deployments effectively capture brute force and botnet attack patterns and enable accurate logging and validation of attack activities. The analysis of false positive rates and structured log validation processes produced more accurate and relevant attack data. This study is among the first to provide a holistic evaluation of Cowrie and Heralding honeypots with direct COBIT 2019 integration, presenting a novel perspective on governance-driven risk management in honeypot implementation. The application of the COBIT framework ensures that honeypot deployment is not only technically effective but also aligned with robust governance and risk management practices for information security. Strategic recommendations are provided regarding configuration optimization, platform selection, and COBIT-based governance integration to enhance organizational cybersecurity resilience